Optimizing HIV retesting during pregnancy and postpartum in four countries: a cost‐effectiveness analysis. Issue 4 (31st March 2021) - Meisner, Julianne; Roberts, D Allen; Rodriguez, Patricia; Sharma, Monisha; Newman Owiredu, Morkor; Gomez, Bertha; de Mello, Maeve B; Bobrik, Alexey; Vodianyk, Arkadii; Storey, Andrew; Githuka, George; Chidarikire, Thato; et al.
Abstract: Introduction: HIV retesting during late pregnancy and breastfeeding can help detect new maternal infections and prevent mother‐to‐child HIV transmission (MTCT), but the optimal timing and cost‐effectiveness of maternal retesting remain uncertain. Methods: We constructed deterministic models to assess the health and economic impact of maternal HIV retesting on a hypothetical population of pregnant women, following initial testing in pregnancy, on MTCT in four countries: South Africa and Kenya (high/intermediate HIV prevalence), and Colombia and Ukraine (low HIV prevalence). We evaluated six scenarios with varying retesting frequencies from late in antenatal care (ANC) through nine months postpartum. We compared strategies using incremental cost‐effectiveness ratios (ICERs) over a 20‐year time horizon using country‐specific thresholds. Results: We found maternal retesting once in late ANC with catch‐up testing through six weeks postpartum was cost‐effective in Kenya (ICER = $166 per DALY averted) and South Africa (ICER=$289 per DALY averted). This strategy prevented 19% (Kenya) and 12% (South Africa) of infant HIV infections. Adding one or two additional retests postpartum provided smaller benefits (1 to 2 percentage point increase in infections averted versus one retest). Adding three retests during the postpartum period averted additional infections (1 to 3 percentage point increase in infections averted versus one retest) but ICERs ($7639 and in Kenya and $11 985 in South Africa) greatly exceeded the cost‐effectiveness thresholds. In Colombia and Ukraine, all retesting strategies exceeded the cost‐effectiveness threshold and prevented few infant infections (up to 31 and 5 infections, respectively). Conclusions: In high HIV burden settings with MTCT rates similar to those seen in Kenya and South Africa, HIV retesting once in late ANC, with subsequent intervention, is the most cost‐effective strategy for preventing infant HIV infections. In these settings, two HIV retests postpartum marginally reduced MTCT and were less costly than adding three retests. Retesting in low‐burden settings with MTCT rates similar to Colombia and Ukraine was not cost‐effective at any time point due to very low HIV prevalence and limited breastfeeding.